Demographic and labor market transformations in rural areas of Chile (2017)
Based on the information provided by the Encuesta de Caracterización Socioeconómica Nacional (CASEN) (National Socioeconomic Characterization Survey) of 1990 and 2013, the reconfigurations of the Chilean countryside are analyzed in terms of their demographic trends and labor market restructuring. An ongoing process of depopulation and aging of the rural population is found. Agricultural activities of the rural labor market become less relevant both in terms of jobs and income, showing a strong process of deagrarianisation, salaried workers and feminization of the labor market.